(untitled) (Revista Latino-Americana de Enfermagem, 2005)
This study aims to discuss the strategies used by the Psychosocial Rehabilitation and Family Health Programs, at a time when a close link is established between psychiatric and basic care. We depart from our own experience in the field and from a literature review, identifying the interfaces and challenges to be overcome with a view to transforming these social contexts into spaces for affective and material exchanges and for more creative and flexible knowledge and practices.